O Compêndio de música de René Descartes - entendimento e anotações sobre a tradução - Castro, Gustavo (2015)
This work focuses on the study of "Compendium Musicae" from the philosopher René Descartes. Translation ipsis literis with the explanations and notes is necessary for a brief analysis of short excerpts of the book. In addition to the translation, our goal is to provide some comments, since the text is unfamiliar and it is also of difficult comprehension, and for satisfactory understanding it is necessary that the reader knows a minimum of theory, rules and musical concepts, and also a minimum about the history that permeates the time when the text was written. Therefore, the unique research focus is Descartes‟ text itself, supported by books that are listed in the research bibliography for further development and understanding of the "Compendium Musicae". In this work, we can see how René Descartes understood music, sound and their interrelationships, therefore formatting a very particular musical aesthetic concept, which appears later at certain times of his life, through his correspondences. We intend that this work can put some light in a work that is still little studied, which presents us the philosopher in his early career, the philosopher that throughout its existence became known and labeled for the strong mathematical appeal, but one day, still young, wrote his first work in which, despite its mathematical trends, brings to the surface his human side.